BS ISO/IEC 30193 AMD1. Information technology. Digitally recorded media for information interchange and storage. 120 mm Triple Layer (100, 0 Gbytes per disk) BD Rewritable disk. (8th March 2020) - British Standards Institution,
No abstract available